Pengaruh Harga, Desain Produk dan Gaya Hidup Terhadap Minat Beli pada Produk Perhiasan Imitasi di Kecamatan Buleleng - Luh Putu Pande Novie Maharani; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2026)
This study aims to analyze the influence of price, product design, and lifestyle on purchase intention toward imitation jewelry in Buleleng District. The population in this study consists of consumers who have an interest in imitation jewelry products in Buleleng District. The sampling technique used is non-probability sampling with a purposive sampling method, involving a total of 160 respondents. The data were collected through the distribution of questionnaires to respondents. The data analysis technique employed in this study is multiple linear regression analysis with hypothesis testing conducted partially (t-test) and simultaneously (F-test). The results of the study indicate that: (1) price has a positive and significant effect on purchase intention toward imitation jewelry in Buleleng District, (2) product design has a positive and significant effect on purchase intention toward imitation jewelry in Buleleng District, (3) lifestyle has a positive and significant effect on purchase intention toward imitation jewelry in Buleleng District, and (4) simultaneously, price, product design, and lifestyle have a significant effect on purchase intention toward imitation jewelry in Buleleng District.